Pinto Saltillo bean yield in high densities under rainfed conditions - Osuna-Ceja, Esteban Salvador; Reyes-Muro, Luis; Padilla-Ramírez, José Saúl; Martínez-Gamiño, Miguel Ángel (Revista Mexicana de Ciencias Agrícolas, 2018)
In order to get high yields from bean varieties cultivated under rainfed conditions is necessary to adapt the agronomic management to the local ecological conditions. This research was carried out to evaluate the yield response of Pinto Saltillo bean variety, with indeterminate prostrate growth habit, at different plant densities (90000, 145000 y 245000 ha-1) and distance between rows (0.76, 0.40 y 0.20 m). Experiments were performed in Sandovales and Pabellón, Aguascalientes, during spring-summer cycles of 2010 and 2011. It was studied three sowing methods (one line in rows of 0.76 m, and 3 and six lines distributed in narrow rows inside beds of 1.52 m wide). Data were recorded on yield and its components. In both years, analyzes of variance for yield and its components showed significant differences () between treatments. The highest yields were obtained by planting three and six rows at densities of 145 000 and 260 000 plants ha-1 respectively. The yield increased 28.6% and 41% by reducing the distance between rows, from the traditional distance of 0.76 m to 0.40 m and 0.20 m, respectively. It was conclude that the variety of bean studied increases its yield under high density of plants even under rainfed conditions in the semiarid regions of Mexico.
Keywords: Phaseolus vulgaris L.; population density; rainfed; triple row; yield